Three-Dimensional Fluoroscopic Navigation Guidance for Femoral Tunnel Creation in Revision Anterior Cruciate Ligament Reconstruction - Taketomi, Shuji (Elsevier, 2012)
Revision anterior cruciate ligament (ACL) reconstruction is accompanied by several technical challenges that must be addressed, such as a primary malpositioned bone tunnel, pre-existing hardware, or bone defects due to tunnel expansion. We describe a surgical technique used to create an anatomic femoral socket using a 3-dimensional (3D) fluoroscopy-based navigation system in technically demanding revision cases. After a reference frame is rigidly attached to the femur, an intraoperative image of the distal femur is obtained, which is transferred to a navigation system and reconstructed into a 3D image. A navigation computer helps the surgeon to visualize the whole image of the lateral wall of the femoral notch, even if the natural morphology of the intercondylar notch has been destroyed by the primary procedure. In addition, the surgeon can also confirm the position of the previous bone tunnel aperture, the previous exit of the femoral tunnel, and the presence of any pre-existing hardware on the navigation monitor. When a new femoral guidewire for the revision procedure is placed, the virtual femoral tunnel is overlaid on the reconstructed 3D image in real time. At our institution, 12 patients underwent 1-stage revision ACL procedures with the assistance of this computer navigation system, and the grafts were securely fixed in anatomically created tunnels in all cases. This technology can assist surgeons in creating anatomic femoral tunnels in technically challenging revision ACL reconstructions.